Choroidal Metastasis from Follicular Cell Thyroid Carcinoma Masquerading as Circumscribed Choroidal Haemangioma - V. P. Papastefanou; A. K. Arora; J. L. Hungerford; V. M. L. Cohen (Case Reports in Oncological Medicine)
Choroidal metastases from follicular thyroid carcinoma are uncommon and usually present as an amelanotic lesion against a background of known systemic disease. We present the case of a 56-year-old woman with a thyroid metastatic focus with unusual clinical presentation, systemic involvement, and early response to systemic treatment. A review of the literature accompanies this case presentation.